The Impact of Consumer Environmental Awareness and Income Level on Green Product Consumption in Indonesia - Andriya Risdwiyanto (North Press, 2025)
This study investigates the impact of consumer environmental awareness and income level on green product consumption in Indonesia using a quantitative research approach. Data were collected from 125 respondents through a structured questionnaire measured on a five-point Likert scale. The collected data were analyzed using SPSS version 25, employing descriptive statistics, validity and reliability tests, and multiple regression analysis. The results reveal that environmental awareness has a positive and significant effect on green product consumption, indicating that consumers who are more knowledgeable and concerned about environmental issues are more likely to purchase environmentally friendly products. Income level also shows a significant positive influence, suggesting that higher purchasing power enables consumers to adopt green consumption practices more consistently. Simultaneously, environmental awareness and income level explain a substantial proportion of the variance in green product consumption behavior. These findings highlight that both psychological and economic factors shape green consumption in Indonesia. The study provides important implications for policymakers and businesses in designing strategies that promote sustainable consumption through environmental education and improved affordability of green products.